The Influence of the Congruence of Organisational Values with Individual Values, Worklife Quality, Organisational Justice on Job Satisfaction and Employee Performance at PT. Brantas Abipraya - Tommy Herdianto; Siti Safaria (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to set a direct and indirect influence of the Congruence of Organizational Values with Individual Values, Work Life quality, Organizational Justice on Employees Job Satisfaction and Employees Performance. The Congruence of organizational values with individual values not impact employees job satisfaction. work life quality impact employee job satisfaction. Organizational justice impact employees job satisfaction. Congruence of organizational values with individual impact employees performance. work life quality impact performance. Organizational justice impact employees performance. Congruence of organizational values with individual values impact employees performance through job satisfaction. work life quality impact employees performance through job satisfaction. Organizational justice indirectly and significantly impact employees performance through job satisfaction. Job satisfaction impact employees performance